4‐1BB costimulation promotes bystander activation of human CD8 T cells. Issue 3 (23rd December 2020) - Reithofer, Manuel; Rosskopf, Sandra; Leitner, Judith; Battin, Claire; Bohle, Barbara; Steinberger, Peter; Jahn‐Schmid, Beatrice
Abstract: Costimulatory signals potently promote T‐cell proliferation and effector function. Agonistic antibodies targeting costimulatory receptors of the TNFR family, such as 4‐1BB and CD27, have entered clinical trials in cancer patients. Currently there is limited information how costimulatory signals regulate antigen‐specific but also bystander activation of human CD8 T cells. Engineered antigen presenting cells (eAPC) efficiently presenting several common viral epitopes on HLA‐A2 in combination with MHC class I tetramer staining were used to investigate the impact of costimulatory signals on human CD8 T‐cell responses. CD28 costimulation potently augmented the percentage and number of antigen‐reactive CD8 T cells, whereas eAPC expressing 4‐1BB‐ligand induced bystander proliferation of CD8 T cells and massive expansion of NK cells. Moreover, the 4‐1BB agonist urelumab similarly induced bystander proliferation of CD8 T cells and NK cells in a dose‐dependent manner. However, the promotion of bystander CD8 T‐cell responses is not a general attribute of costimulatory TNF receptor superfamily (TNFRSF) members, since CD27 signals enhanced antigen‐specific CD8 T cells responses without promoting significant bystander activation. Thus, the differential effects of costimulatory signals on the activation of human bystander CD8 T cells should be taken into account when costimulatory pathways are harnessed for cancer immunotherapy. Abstract : Using a novel system of engineered antigen presenting cells (eAPC), we demonstrate that 4‐1BB signals generated by 4‐1BBL or agonistic 4‐1BB antibodies promote bystander activation of human CD8 T cells